Application of Hereditary Renal Cell Carcinoma Risk Criteria to a Large Prospective Database. Issue 1 (January 2020) - Kushnir, I.; Kirk, L.; Mallick, R.; Kim, R.H.; Graham, G.E.; Breau, R.H.; Lattouf, J.-B.; Violette, P.D.; Pautler, S.E.; Care, M.; Kapoor, A.; Jewett, M.A.S.; et al.
Abstract: Aims: To evaluate the clinical impact of the Canadian criteria for identifying patients and families at risk for hereditary renal cell carcinoma (RCC). Materials and methods: The Canadian hereditary RCC risk criteria were applied to patients from 16 centres in the Canadian Kidney Cancer information system (CKCis) prospective database. The primary end point was the proportion of patients who met at least one criterion. Results: Between January 2011 and May 2017, 8388 patients were entered in the database; 291 had inadequate risk data; 2827 (35%) met at least one criterion for genetic testing (at-risk population). Most (83%) met just one criterion. The criterion of non-clear cell histology contributed the largest proportion of at-risk patients (59%), followed by age ≤ 45 years (28%). Sixty-one patients had documentation of genetic testing, with 56 being classified at-risk (2% of at-risk). Twenty patients (35%) of the patients at risk and tested for hereditary RCC were found to harbour a germline mutation. Conclusions: Application of the Canadian hereditary RCC risk criteria to a large prospective database resulted in 35% of patients being identified at risk for hereditary RCC who could qualify for genetic testing. However, the true incidence of hereditary RCC in this population is unknown as most patients did not have documented genetic testing carried out and, thus, the sensitivity and specificity of the criteria cannot be determined. The low proportion of at-risk patients who underwent genetic testing is disappointing and highlights that there may be gaps in reporting, knowledge and/or barriers in access to genetic testing. Highlights: 2827 patients (35% of patients diagnosed with RCC) met the criteria for at risk for hereditary RCC. 56 of the patients at risk were tested and 35% of them were found to harbour a germline mutation. Low proportion of at-risk patients were referred for genetic testing. Research is warranted to identify barriers to referrals and testing.